LEUKEMIA SEL BERAMBUT - Reini Meilani Isbach; Agus Alim Abdullah; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Hairy cell leukaemia (HCL) is a neoplastic disorder of B lymphocytes originally described by Bouroncle et al. in 1958. HCL clinicalmanifestations varies, generally characterized by various degrees of splenomegaly, pancytopenia, or emphasis only on the two cell lines(bisitopenia), with the hairy cells in varying amounts in the peripheral blood smear and bone marrow. HCL is a very rare case, there areonly about 2% of all leukaemias more frequently in men than women (4:1) with the average age of disease onset between 50–55 years.The etiology of HCL is still not known. A case of HCL Leukaemia in a female patient, aged 55 years is reported which was a rare case.HCL diagnosis in this patient was based on the clinical manifestation (splenomegaly), and laboratory results (bisitopenia, neutropeniaand monositopenia) and about 80% hairy cells were found in peripheral blood smears. Definite diagnosis of HCL should be made by bonemarrow examination, immunophenotyping and cytogenesis.